Geometry of strongly minimal hybrids of fragments of theoretical sets - Kassymetova, M.T.; Mussina, N.M. (Bulletin of the Karaganda University. Mathematics series, 2023)
In this article, strongly minimal geometries of fragment hybrids are considered. In this article, a new concept was introduced as a family of Jonsson definable subsets of the semantic model of the Jonsson theory T, denoted by JDef(CT ). The classes of the Robinson spectrum and the geometry of hybrids of central types of a fixed RSp(A) are considered. Using the construction of a central type for theories from the Robinson spectrum, we formulate and prove results for hybrids of Jonsson theories. A criterion for the uncountable categoricity of a hereditary hybrid of Jonsson theories is proved in the language of central types. The results obtained can be useful for continuing research on various Jonsson theories, in particular, for hybrids of Jonsson theories.
Keywords: Jonsson theory; semantic model; fragments; hybrid of Jonsson theories; Jonsson set; theoretical set; central type; pregeometry; Robinson theory; strongly minimal type